2012
DOI: 10.5171/2012.983677
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internal R&D in Operational Performance as Moderated by Intellectual Property Rights: The Malaysian Manufacturing Perspective

Abstract: This paper reviews the role played by a company's internal R&D in stimulating operational performance of a manufacturing company, which is moderated by intellectual property rights (IPR), particularly patents, in Malaysia. The constructs of this paper are based on a comprehensive review of recent literature on internal R&D and operational performance moderated by patents. A detailed discussion revealed implications on policy making, especially for government or related authorities in promoting and enforcing IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Among various R&D capabilities, intellectual property right (IPR) is the core element which is the protection of one's own effort in the creation of new inventions or products. For enhancing R&D toward OP, IPR acts as a stimulus [38].…”
Section: Research and Developmentmentioning
confidence: 99%
“…Among various R&D capabilities, intellectual property right (IPR) is the core element which is the protection of one's own effort in the creation of new inventions or products. For enhancing R&D toward OP, IPR acts as a stimulus [38].…”
Section: Research and Developmentmentioning
confidence: 99%
“…The majority of those studies appear to have identified a positive relationship between a firm's investment in intellectual property and its business performance, and its financial performance in particular. Representative examples include: Anuar, et al (2012), wide variety of manufacturing industries in Malaysia; Bollen, et al (2005), pharmaceuticals industry in Germany; Bosworth and Rogers (2001), wide variety of large, publicly traded firms in Australia; Cohen and Kaimenakis (2007), service-sector firms in Greece; Graham and Sichelman (2008), literature survey and wide variety of technology start-up firms in the United States; Greenhalgh and Longland (2005), Greenhalgh andRogers (2006 &2007), wide variety of manufacturing firms in the United Kingdom; Hanel (2008), manufacturing firms from many industries in Canada; Hsu and Ziedonis (2013), semiconductor firms in the United States; Juma and McGee (2006), technology firms from eleven different industries in the United States; Lichtenthaler (2009), European-wide study, many industries; Namvar, et al (2010), electronics and computing firms in Iran; Pandit,, et al (2011), multi-national study, broad variety of technology-intensive industries and sectors; Roy (2013), information technology firms in India; and, Suh and Hwang (2010), computer software firms in South Korea.…”
Section: Intellectual Property and The Financial Performance Of Firmsmentioning
confidence: 99%
“…Hence, integrating the chemical storage business with the current normal warehouse business is crucial. This is echoed by Anuar et al (2012), who supported the argument that internal R&D within the organization gives added value to the company in the long run.…”
Section: Chemical Industry Outlookmentioning
confidence: 93%
“…The company may gain advantages and added value in three aspects, namely the ability to develop and grow critical human resources, dynamic involvement in the corporate R&D programme, and the ability to connect information. (Anuar, Zulhumadi, & Udin, 2012).…”
Section: Introductionmentioning
confidence: 99%